Study on the behavior of the Minimum quantity lubricant - MQL technique under different lubricating and cooling conditions when grinding ABNT 4340 steel - Silva, L. R.; Bianchi, E. C. [UNESP]; Catai, R. E. [UNESP]; Fusse, R. Y. [UNESP]; França, T. V. [UNESP]; Aguiar, P. R. [UNESP] (Springer Nature, 2005)
The behavior of the minimum quantity lubricant (MQL) technique was analyzed under different lubricating and cooling conditions when grinding ABNT 4340 steel. The comparative analysis of the residual stress values showed that residual compressive stresses were obtained under all the lubrication/cooling conditions and types of abrasive tools employed. The highest residual compressive stress obtained with the aluminum oxide grinding wheel with MQL under the condition of V= 30m/s for air and V= 40ml/h for lubricant was -376MPa against the -160MPa attained with conventional cooling, representing a 135% increase in residual compressive stress. The results show that method and quantity of lubricant and cooling are factors that influence the grinding process.
Keywords: CBN and MQL; G ratio; Grinding; Residual stress; Roughness; Tangential cutting force; Cooling; Cutting; Grinding (comminution); Lubricants; Machining; Residual stresses; Surface roughness; Testing; Cubic boron nitride (CBN); Minimum quantity lubricant (MQL); Stainless steel